2016
DOI: 10.3390/ijms17122062
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasminogen Activator Inhibitor-1 (PAI-1) Gene Polymorphisms with Osteoporotic Vertebral Compression Fractures (OVCFs) in Postmenopausal Women

Abstract: Osteoporosis and osteoporotic fractures are strongly associated with mortality and morbidity, both in developing and developed countries. Menopause accelerates bone loss due to estrogen deficiency and age-related linear bone loss. We investigated plasminogen activator inhibitor-1 (PAI-1) gene polymorphisms in postmenopausal women with osteoporotic vertebral compression fractures (OVCFs). In this case-control study, 355 postmenopausal women were genotyped for the presence of PAI-1 gene polymorphisms −844A > G, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
1
10
0
1
Order By: Relevance
“…PAI‐1 is expressed by osteoblasts and osteoclasts, and its expression is stimulated by several cytokines . Polymorphisms in PAI‐1 are associated with the incidence of osteoporotic vertebral compression fractures , although serum PAI‐1 levels and functional studies for PAI‐1 single nucleotide polymorphisms (SNPs) were not examined in this study. Several studies using PAI‐1‐deficient mice have indicated involvement of the plasminogen activator/PAI‐1 system in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PAI‐1 is expressed by osteoblasts and osteoclasts, and its expression is stimulated by several cytokines . Polymorphisms in PAI‐1 are associated with the incidence of osteoporotic vertebral compression fractures , although serum PAI‐1 levels and functional studies for PAI‐1 single nucleotide polymorphisms (SNPs) were not examined in this study. Several studies using PAI‐1‐deficient mice have indicated involvement of the plasminogen activator/PAI‐1 system in bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…OVCFs have a profound impact on patients with spinal kyphosis and lumbar back pain; if not treated in time, patients will suffer persistent pain, needing treatment with analgesic drugs daily to maintain normal life; not only does it increase the financial burden, but it also has a serious impact on the physical and mental health and the quality of life ( 16 ). The results of this study show that there were no significant differences in preoperative ODI, MPQ and JOA scores between the two groups (P>0.05), and after operation, the scores of ODI, MPQ and JOA in the two groups were significantly improved, which were more obvious in the observation group than those in the control group (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A probability ( p ) value of 0.05 was considered to indicate statistical significance. ORs were adjusted by possible confounders, including age, hypertension, and DM [ 58 ]. These parameters were selected as adjustment variables because they are directly or potentially associated with OVCF.…”
Section: Methodsmentioning
confidence: 99%